Intertextuality in Academic Writing: Teaching Students to Weave Stronger Arguments - Yulandari, Evi Safitri; Alfarisi, Salman (Journal of Advance in Language, Literature, and Education, 2025)
Intertextuality is a crucial yet often overlooked aspect of academic writing that enables students to construct well-supported and persuasive arguments. This article explores how teaching intertextuality enhances students' ability to integrate sources effectively, establish connections between ideas, and develop a strong academic voice. By examining various forms of intertextual references—such as direct quotations, paraphrases, summaries, and implicit allusions—this study highlights strategies to improve coherence and argumentation in student writing. Furthermore, it discusses how a deeper understanding of intertextuality can help students avoid unintentional plagiarism while strengthening their critical thinking skills. The article also presents pedagogical approaches, including scaffolded exercises and reflective writing, to help students engage with texts more meaningfully. By fostering an awareness of intertextuality, educators can empower students to participate more confidently in academic discourse, constructing arguments that are both original and well-grounded in existing literature.